The Use Of B. Bloom’s Taxonomy Of Educational Goals Of In The Formation Of Linguo-Methodical Competences Of Future Primary School Teachers - Sadikov, Rustam Mansurovich (The journal of contemporary issues in business and government, 2021)
The article reveals the results of an experiment conducted at the bases of the Tashkent State Pedagogical University named after Nizami, Andijan State University and Jizzakh State Pedagogical Institute. The experiment took place within the framework of the dissertation research on the topic of "The Methodology for the formation of linguo- methodological competences of future primary school teachers", where B. Bloom's Taxonomy of Educational Goals was chosen as a diagnostic and corrective tool.